2020
DOI: 10.21548/41-2-4016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aroma and Sensory Properties of Prokupac Wines by a Bacillus-based Preparation Applied to Grapes Prior to Harvest

Abstract: Modern viticulture requires the replacement of hazardous agrochemicals with eco-friendly, bio-based products such as microbial preparations that enhance grape and wine quality while protecting the grapevine from pest and disease attacks. This study investigated the effects of a commercially available Bacillusbased preparation on the volatile and sensory properties of wines made from Vitis vinifera, cv. Prokupac grapes. Three different concentrations of preparation based on Bacillus subtilis Ch-13 were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Further, it was shown that yeast strain used for the fermentation did not significantly influence total wine acidity, while significantly lower volatile acidity was detected in both samples fermented with C. famata (pure or sequential) compared to the control sample. The total (titratable) and volatile acidity for both samples produced with C. famata isolate were consistent with previously published results for the monovarietal Prokupac wines [20,22]. Beside the total acidity, it was proven that organic acid profile is strongly correlated with wine overall quality and sensory characteristics [38,39].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, it was shown that yeast strain used for the fermentation did not significantly influence total wine acidity, while significantly lower volatile acidity was detected in both samples fermented with C. famata (pure or sequential) compared to the control sample. The total (titratable) and volatile acidity for both samples produced with C. famata isolate were consistent with previously published results for the monovarietal Prokupac wines [20,22]. Beside the total acidity, it was proven that organic acid profile is strongly correlated with wine overall quality and sensory characteristics [38,39].…”
Section: Discussionsupporting
confidence: 90%
“…Prokupac is an autochthonous red grape variety characteristic for the central part of Serbia with long use in wine production [20]. Prokupac wine has unique phenolic profile with high content of anthocyanins, flavonols, flavon-3-ols monomers and hydroxybenzoic acid derivatives which contribute to expressive antioxidant activity [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Ampelomyces quisqualis, Trichoderma harzianum, T. asperellum, T. virens, Pythium oligandrum, Pseudozyma flocculosa, Bacillus subtilis, B. licheniformis, B. brevis, B. cereus, Pseudomonas fluorescens , and Streptomyces cacaoi were noteworthy (Rao et al, 2015 ; Damalas and Koutroubas, 2018 ; Thakur et al, 2020 ; Salimi and Hamedi, 2021 ). However, very few microbe-based products/technologies are available in the market for wider applicability in the Indian subcontinent and abroad to control grape powdery mildew in the organic viticulture (Compant et al, 2013 ; Moyer et al, 2016 ; Cangi et al, 2018 ; Malićanin et al, 2020 ). Due to a lack of information in the scientific literature on the availability and effectivity of microbial inoculants, agronomists and vine growers are often not aware of these new products and the impact they can have indirectly on the quality of grapes (Lu W. et al, 2020 ; Agbowuro et al, 2021 ; Steiner et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%